ANALYSIS OF LEAN SIGMA - DMAIC IMPLEMENTATION WITH ENVIROMENTAL CONSIDERATIONS IN OIL & GAS INDUSTRY (CASE STUDY: ONSHORE FIELD ABC TERMINAL FIELD – PT XYZ) - Gugi Agusman Setiamitra; Athor Subroto (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
The oil and gas industry is facing increasing pressure from an operations and environmental compliance perspective. The adoption of Lean Sigma methodology has been shown to improve the operational performance of various industries, including the Oil and Gas industry.Â The objective of this research is to analyse the implementation of a sustainable improvement framework based on the Lean Sigma DMAIC (define-measure-analyse-improve-control) method, considering the environment in maintaining sustainable business in the oil and gas industry. The research action approach in a case study is used to illustrate the application of the proposed Lean Sigma - DMAIC framework to improve operational performance and the environment in the oil and gas industry. The case study illustrates the application of the Lean Sigma - DMAIC cycle to improve crude oil quality â€“ Base sedimen & water (BS&W) product and optimize energy consumption in the processing of crude oil. After improving the quality of oil production that previously experienced deviations and making improvements and efficiencies in the processing plant, this oil processing plant can achieve operational cost savings of US 181,847.95 and environmental benefits in reducing CO2 emissions by 1,685.81 tons (CO2 eq) by reducing the gas consumption used to heat crude oil in the oil treating plant.